Facile Synthesis of Fe3o4 Nanoparticles at Room Temperature Coated with Meso-2,3-Dimercaptosuccinic Acid for Improved Biocompatibility - Oyarzun-Medina, S; Casagrande-Denardin, J (Springer Science and Business Media B.V., 2023)
Superparamagnetic magnetite Fe3O4 nanoparticles (NPs) were synthesized by the coprecipitation method and stabilized with meso-2,3-dimercaptosuccinic acid (DMSA) under ambient conditions and a nitrogen atmosphere at room temperature in one simple step. The X-ray diffraction (XRD) analysis of Fe3O4 NPs confirmed their cubic spinel structure with high crystallinity for both samples prepared with or without nitrogen atmosphere. The scanning electron microscopy analysis showed an average particle size of 15.0 ± 3 nm and 23.0 ± 5 nm in the absence and presence of nitrogen, respectively. Our particles have shown excellent magnetic properties with a high saturation magnetization (55 emu/g), low remanence (3.0 emu/g), and low coercivity (43 Oe). The method of synthesis proposed here offers excellent reproducibility of superparamagnetic NPs with narrow size distribution and low aggregation despite the simplicity of its preparation. The dose–response curves of the colorimetric assay MTT carried out in HCT 116 cell cultures in a range from 30 to 250 μg/mL reveal that magnetic nanoparticles coated with DMSA significantly improve their biocompatibility for applications like magnetic hyperthermia, magnetic resonance imaging, or biosensing. Graphical Abstract: [Figure not available: see fulltext.]. © 2023, The Author(s), under exclusive licence to Springer Nature B.V.